Education of the Character of the Main Characters in the Novel Merasa Pintar, Bodoh Saja Tak Punya by Rusdi Mathari (Analysis of Literature Psychology) - Charin Setya Handayani; Sudiatmi, Titik; Suparmin (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This research aims to describe how the character in the main character and also the structure of his personality, especially about character education in the novel by Rusdi Mathari entitled